Biochemical parameters in patients with Trichomonasvaginalis and Toxoplasma gondii in Erbil-Iraq - Abdul-Aziz Kadir, Mohammed; RafikHamad, Narmeen (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study investigated the biochemical parameters of two parasites, Trichomonasvaginalis and Toxoplasma gondii among females attending the gynaecological out patients clinics in MaternityRizgaryHospital, several health centers and some private clinics in Erbil-Iraq, from 16th July 2007 till 15th July 2008, by using different diagnostic methods. In addition, a comparative study to evaluate the biochemical changes due to tichomoniasis and toxoplasmosis. The serum samples were examined for some biochemical parameters like cholesterol, triglycerides, high density lipoproteins-cholesterol (HDL-C), low density lipoproteins-cholesterol (LDL-C), total proteins, albumin, globulin, with some elements such as calcium, sodium, potassium, chloride, iron, copper and zinc. Infection with Trichomonasvaginalis had no significant effects on the studied biochemical parameters among non-pregnant women. Toxoplasma gondii causes a significant decrease in total protein level among non-pregnant women, while in pregnant women, reduced calcium level was observed